Analisis Simpanan Terhadap Sisa Hasil Usaha Anggota Koperasi Tekad Waras Dinas Pendidikan Di Kabupaten Lebak - Hayatinufus Siatan; Lita Mulyati; Khaeriyatun Nisa (E-Journal Studia Manajemen, 2014)
Deposits member is an important problem in running a business case for the cooperative. Availability of member savings that act as sufficient capital will determine the smoothness of the cooperative effort and conversely the lack of capital could hamper the smooth operation of the business. This research was conducted at the Cooperative Tekad Waras Rangkasbitung determination using quantitative research method possible with a sample size of 10 years from 2004 to 2013 with the collection of data through observation and documentation as well as the use of data analysis with SPSS version 20. From the analysis results obtained by using the product moment correlation shows a very strong relationship in both variables. Coefficient of determination shows that a variable Y can be affected by variables X, based on the results obtained by linear regression analysis of the linear regression equations with constant coefficients and coefficients of variables that exist in column B